Online clothes selling and donation management system - Wong, Teng Wei (2023)
In this era of rapid technological advancement and heightened living standards, the ubiquitous accessibility of information and innovative tools stands out. Yet, the surging issue of textile waste, propelled by the fast fashion phenomenon, casts a shadow. Even with a growing recycling consciousness, affordable and transient fashion trends exacerbate textile discard rates, directing a concerning volume into landfills. To address this, this study introduced a mobile application tailored to facilitate sustainable wardrobe management. Employing the Agile Development methodology and crafted using Android Studio with Firebase integration, the system boasted three distinctive features: an online marketplace for reselling secondhand clothing, a dedicated platform for users to donate their apparel to charitable organizations, and a unique rewards system. This reward feature incentivizes and acknowledges users for their charitable donations, further encouraging sustainable practices. The Agile approach segmented the project into focused sprints, emphasizing continuous integration, testing, and adaptability rooted in real-time feedback. Upon completion, user testing was initiated, with feedback overwhelmingly positive. Users lauded the intuitive interface, smooth marketplace transactions, effortless donation processes, and the rewarding experience offered, confirming the application's efficacy in addressing textile waste and promoting environmentally conscious behaviors. In the evolving landscape of technology and sustainable practices, the system was developed with objectives centering around combating the "throwaway" culture, providing an integrated solution for selling and donating old clothes, and enhancing user experience with a rewarding and intuitive interface. These objectives were realized as users now have a seamless platform that not only encourages the resale and donation of clothing but also incentivizes sustainable behavior through an innovative rewards system, all while offering advanced search capabilities and promoting a reduced textile waste footprint.